ANALISIS SEKTOR EKONOMI UNGGULAN DAN HUBUNGANNYA DENGAN KESEMPATAN KERJA DAN INVESTASI DI KABUPATEN BATANGHARI - Ahmad Soleh; Hamdi Sari Maryoni (FEB Universitas Sultan Ageng Tirtayasa, 2017)
In spurring economic growth, leading sectors have a very central role. Aside from being an effective sector has also become a driving force in developing sectors other sectors. On the basis of the economic sector it is very necessary to analyze the various approaches and theories. The study, entitled